Cardiovascular health profile among Québec male and female police officers. Issue 6 (2nd November 2019) - Gendron, Philippe; Lajoie, Claude; Laurencelle, Louis; Trudeau, François
Abstract: To document the cardiovascular health profile of Québec police officers (PO). Participants answered an online questionnaire evaluating the presence of cardiovascular disease (CVD) risk factors and symptoms. Two thousand, ninety-nine (2, 099) male (age: 40.8 ± 9.2 years) and 756 female (age: 37.9 ± 7.9 years) PO participated in this study. The prevalence of obesity (body mass index ≥30 kg/m 2 ) and diagnosed hypertension was respectively 21.1, and 14.3% in male and 7.3 and 4.1% in female PO. According to 2013 American College of Sports Medicine guidelines, 27.0 and 48.0% of male and 12.1 and 56.7% of female PO were categorized as being at moderate and high CVD risk, respectively. These findings suggest that Québec police departments should help PO to adopt and maintain a healthy lifestyle to decrease CVD risk.